THE EFFECT OF PERCEIVED QUALITY, BRAND IMAGE ON CUSTOMER SATISFACTION AND BRAND AWARENESS TOWARD REPURCHASE INTENTION - IZZUDIN, MUHAMMAD SIDI; NOVANDARI, WENI (INDONESIAN RESEARCH SOCIETY, 2018)
The purpose of this study is to analyze the factors that affect the repurchase intention, whichis brand awareness and customer satisfaction, and the customer satisfaction affected byperceived quality and brand image. The population in this study is Indocafe coffeecostumers in Purwokerto. The total number of samples that used in this study was 120respondents by using convenience sampling. The measurement of variables in this researchusing Likert's scale and hypothesis testing using Structural Equational Modeling (SEM).Based on the result of this study, the average of respondent is male between the ages of20-30 years old and the favorite is Indocafe Coffeemix 3 in 1. The result shows that (1)Perceived quality has a positive effect on customer satisfaction, (2) Brand image has apositive effect on customer satisfaction, (3) Customer satisfaction has a positive effect onbrand awareness, (4) Customer satisfaction has a positive effect on repurchase intention,and (5) Brand awareness has a positive effect on repurchase intention. a. Perceived qualityis a factor that effect the costumer satisfaction and impacts the repurchase intention. Bymaintaining the quality of taste and aroma of Indocafe coffee consumers will be moresatisfied and have an impact on future intention.